2014
DOI: 10.1002/elan.201400313
|View full text |Cite
|
Sign up to set email alerts
|

Gold and Nanogold Electrodes Modified with Gold Nanoparticles and meso‐2,3‐Dimercaptosuccinic Acid for the Simultaneous, Sensitive and Selective Determination of Dopamine and Its Biogenic Interferents

Abstract: Gold and nanogold electrodes modified with self‐assembled layers composed of gold nanoparticles and organic sulfur compounds were applied for quantitative determination of dopamine and its biogenic interferents like: ascorbic and uric acids. For the novel sensor a linear relationship between the current response of dopamine at the potential of peak maximum and the concentration was found over a wide analyte concentration range in solution with a very good detection sensitivity and detection limit. It was prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The earlier [17,35,37,44,56] and present studies have shown that the gold sol obtained by the Turkevich method [46] used in this work contains gold nanoparticles of the average diameter of about 16 nm, as evaluated from the transmission electron microscopy image (TEM) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The earlier [17,35,37,44,56] and present studies have shown that the gold sol obtained by the Turkevich method [46] used in this work contains gold nanoparticles of the average diameter of about 16 nm, as evaluated from the transmission electron microscopy image (TEM) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 53%
“…It should be emphasized that the lower the detection limit, the lower the analyte concentration that can be detected. For a comparison of the dopamine c L obtained on the prepared, in this work, electrode with the other ones obtained on different Au-modified electrodes, see [35,37].…”
Section: Quantitative Analysis Of Dopamine Electrooxidationmentioning
confidence: 99%
See 3 more Smart Citations